2020
DOI: 10.3389/fpsyg.2019.02871
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Embodiment on Emotional Categorization of Faces and Words in Children and Adults

Abstract: The facial feedback hypothesis (FFH) indicates that besides being involved in the production of facial expressions, the musculature of the face also influences one's perception of emotional stimuli. Recently, this effect has been the focus of increased scrutiny as efforts to replicate a key study with adult participants supporting this hypothesis, using the so-called "pen-in-the-mouth" task, have not been successful at several labs. Our series of experiments attempted to investigate whether the assumed embodim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In addition to language differences, affective meanings of words seem to vary with age. Age-related differences in emotional context have been evidenced when words were rated by children and adults (Monnier and Syssau, 2017 ; Vesker et al, 2018 , 2020 ; Morningstar et al, 2019 ; Sabater et al, 2020 ). The available evidence suggested that young children's ratings of valence were more extreme than those of adolescents and adults (Monnier and Syssau, 2017 ; Vesker et al, 2018 ).…”
Section: Age-related Differences In Emotional Functionsmentioning
confidence: 99%
“…In addition to language differences, affective meanings of words seem to vary with age. Age-related differences in emotional context have been evidenced when words were rated by children and adults (Monnier and Syssau, 2017 ; Vesker et al, 2018 , 2020 ; Morningstar et al, 2019 ; Sabater et al, 2020 ). The available evidence suggested that young children's ratings of valence were more extreme than those of adolescents and adults (Monnier and Syssau, 2017 ; Vesker et al, 2018 ).…”
Section: Age-related Differences In Emotional Functionsmentioning
confidence: 99%